Effect of density variation method and air humidity consideration on the computational simulation of solar vortex power generation systems - Tukkee, A.M. (2023)
The flow inside solar vortex systems is complicated and requires a large effort by numerical simulation. This study presents a contribution to CFD methods to study solar vortex systems. The incompressible ideal gas law and the Boussinesq approximation have been compared, and the differences in flow results are discussed. The system is studied further to explore the effect of air humidity on the properties of the vortex field and power potential. It was found that the incompressible ideal gas law, considering the operating density should be specified at the ambient conditions, is a better choice than the widely used Boussinesq approximation. The computational demands for both methods are the same. The Boussinesq approximation resulted in a 0 density change at the same solar and ambient conditions. In comparison, the incompressible ideal gas law has resulted in a 4.25 change in the air density between the top of the vortex and the ambient air and 0.5 between the top of the vortex and the inlet of the vortex generator. Results show that humidity is very important to be considered in the determination of the properties, in particular, the pressure drop potential in the simulation of the solar vortex system. As the moisture content is higher, the pressure drop in the flow reduces, reducing the power output. Under similar solar and climate conditions, the static pressure drop at the top of the vortex domain is 8.5, 8.1 and 7.7 Pa for cases of dry air, 40 and 80 relative humidity air, respectively. Â© 2022 Elsevier Ltd